Enel X : driving digital transformation in the energy sector - Chesbrough, Henry (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2020)
Enel is one of the world's largest electric utilities, based in Italy but operating in dozens of countries around the world. This case discusses the process of establishing a new subsidiary company inside Enel to lead the company towards digital transformation in eMobility. The new entity must manage a number of legacy businesses, and also foster a new and different culture in an environment where no one is easily fired. It also must self-finance the transformation, without much upfront investment from the parent organization. In the case, the CEO takes stock of his actions so far, and seeks to chart a course for the future.
Originally Published InChesbrough, H. (2020). Enel X: Driving Digital Transformation in the Energy Sector. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Self-financing.; Corporate culture